Paleozoic multi-stage magmatism in the Yuka terrane, North Qaidam orogenic belt: mantle modification, tectonic evolution, and geodynamic processes - Lin, Yibin; Yu, Chengtao; Chen, Shuyuan; Shi, Sudong; Luo, Sangjiancuo; Khan, Junaid (Frontiers in Earth Science, 2025)
The detailed study of HP/UHP metamorphic rocks and intermediate-acid rocks has revealed the complete tectonic evolution of the North Qaidam Orogenic Belt (NQOB), from oceanic to continental subduction and subsequent exhumation. However, less comprehensive studies of Paleozoic mafic rocks have led to a limited understanding of the subcontinental lithospheric mantle, geodynamic settings, and tectonic transitions. In this paper, a comprehensive study of mafic-intermediate rocks from the Yuka Terrane in the NQOB suggests that zircon U-Pb dating yielded ages of 471 ± 3 Ma and 438 ± 3 Ma, respectively. Both rocks exhibit arc-like trace element patterns, characterized by enrichment in REEs and LILEs (e.g., Cs, Rb, Ba, Th), depletion in HFSEs (e.g., Nb, Ta), moderate (⁸⁷Sr/⁸⁶Sr) i values (ranging from 0.70473 to 0.70811 and 0.70599 to 0.70685, respectively), and εNd(t) values ranging from positive to negative (−2.7 to +0.3 and −1.0 to +1.5, respectively), indicating derivation from the partial melting of enriched subcontinental lithospheric mantle. The current trace element compositions and previous studies on post-collisional mafic rocks suggest that the enriched material added to the subcontinental lithospheric mantle beneath the Qilian Block is primarily derived from fluids released by the subducting oceanic crust, with a smaller contribution from melts of overlying sediments. A comparison with previous studies, including mafic geochronological data and the period of UHP metamorphism, reveals that Paleozoic magmatism in the NQOB can be divided into three stages, while the NQOB experienced four distinct stages of geodynamic processes. These findings suggest a model of tectonic evolution and geodynamic transition: (1) 535–445 Ma: Slab retreat and associated back-arc extension; (2) 445–420 Ma: Slab rollback; (3) 420–395 Ma: Slab breakoff; (4) 395–360 Ma: Orogenic lithospheric collapse and extension. Overall, this study provides new insights into the nature of the subcontinental lithospheric mantle beneath the Qilian Block, as well as the tectonic evolution and geodynamic processes within the NQOB.